A network meta-analysis: The best Yiqi Fuzheng Chinese herbal injections for use based on the NP regimen to treat NSCLC. Issue 31 (31st July 2020) - Luo, Huiyan; Zheng, Wenjiang; Yan, Qian; Wang, Boqing; Ye, Baoqian; Deng, Shicong; He, Fan; Yang, Xinqian; Wang, Xiongwen
Abstract: Background: Chinese herbal injections (CHIs) have been proven beneficial to patients with non-small cell lung cancer (NSCLC) in combination with chemotherapy. The network meta-analysis (NMA) was designed to update and expand on previous work to better evaluate the effectiveness and safety of different Yiqi Fuzheng (YQFZ) CHIs combined with the Vinorelbine plus cisplatin (NP) regimen versus NP alone for NSCLC. Methods: We searched multiple electronic databases and identified randomized controlled trials (RCTs) concerning different YQFZ CHIs combined with the NP regimen for treating NSCLC up to March 1st, 2019. The outcomes are the objective response rate, performance status and adverse reactions (ADRs). Two individuals accomplished the quality assessment of this NMA based on the Cochrane risk of bias tool and the methodological section of the CONSORT statement. Random effects models were generated to estimate efficacy and safety outcomes. Odds ratios and corresponding 95% confidence intervals were calculated via Stata 14 software. Furthermore, the rankings for the efficacy and safety of different YQFZ CHIs for each outcome were determined by the surface under the cumulative ranking curve (SUCRA). Results: Initially, a total of 4775 citations were retrieved through comprehensive searching, and 88 eligible articles involving 6695 participants and 8 CHIs were ultimately included. The cluster analysis results of the current evidence indicated that the NP regimen combined with Delisheng, Shenfu and Shenmai injections have a higher clinical effectiveness rate and better performance status compared with the NP regimen alone. Additionally, the NP regimen combined with Shenqifuzheng, Shengmai and Shenfu injections may be considered a favorable choice for reliving ADRs among patients with NSCLC. Conclusions: The current evidence demonstrated that the combination of Shenfu injection plus NP regimen could produce better outcomes than other YQFZ CHIs groups in terms of efficacy and safety. However, meticulously designed, strictly executed, high-quality trials are still required to further assess and confirm the results due to the inadequacy of the included RCTs. Abstract : Supplemental Digital Content is available in the text